Histone Deacetylase 5 Is an Early Epigenetic Regulator of Intermittent Hypoxia Induced Sympathetic Nerve Activation and Blood Pressure - Wang, Ning; Peng, Ying-Jie; Su, Xiaoyu; Prabhakar, Nanduri R.; Nanduri, Jayasri (Frontiers in Physiology, 2021)
Intermittent hypoxia (IH) is a hallmark manifestation of obstructive sleep apnea (OSA). Long term IH (LT-IH) triggers epigenetic reprogramming of the redox state involving DNA hypermethylation in the carotid body chemo reflex pathway resulting in persistent sympathetic activation and hypertension. Present study examined whether IH also activates epigenetic mechanism(s) other than DNA methylation. Histone modification by lysine acetylation is another major epigenetic mechanism associated with gene regulation. Equilibrium between the activities of histone acetyltransferases (HATs) and histone deacetylases (HDACs) determine the level of lysine acetylation. Here we report that exposure of rat pheochromocytoma (PC)-12 cells to IH in vitro exhibited reduced HDAC enzyme activity due to proteasomal degradation of HDAC3 and HDAC5 proteins. Mechanistic investigations showed that IH-evoked decrease in HDAC activity increases lysine acetylation of α subunit of hypoxia inducible factor (HIF)-1α as well as Histone (H3) protein resulting in increased HIF-1 transcriptional activity. Trichostatin A (TSA), an inhibitor of HDACs, mimicked the effects of IH. Studies on rats treated with 10 days of IH or TSA showed reduced HDAC activity, HDAC5 protein, and increased HIF-1 dependent NADPH oxidase (NOX)-4 transcription in adrenal medullae (AM) resulting in elevated plasma catecholamines and blood pressure. Likewise, heme oxygenase (HO)-2 null mice, which exhibit IH because of high incidence of spontaneous apneas (apnea index 72 ± 1.2 apnea/h), also showed decreased HDAC activity and HDAC5 protein in the AM along with elevated circulating norepinephrine levels. These findings demonstrate that lysine acetylation of histone and non-histone proteins is an early epigenetic mechanism associated with sympathetic nerve activation and hypertension in rodent models of IH.